Weak lensing effect on CMB in the presence of a dipole anisotropy - Abhineet Agarwal; Naveen K. Singh; Pankaj Jain; Prabhakar Tiwari (European Physical Journal C: Particles and Fields, 2019)
Abstract We investigate weak lensing effect on cosmic microwave background (CMB) in the presence of a superhorizon mode which leads to a dipole anisotropy in the CMB power spectrum and in large scale structures. The approach of flat-sky approximation is considered. We determine the functions $$σ _0^2$$ σ02 and $$σ _2^2$$ σ22 that appear in expressions of the lensed CMB power spectrum in the presence of the dipole anisotropy. We determine the correction to B-mode power spectrum which is found to be appreciable at low multipoles (l), around $$15%$$ 15% at $$l=10$$ l=10 . However, the temperature and E-mode power spectrum are not altered significantly.